(untitled) (Revista Brasileira Multidisciplinar, 2015)
The aim of this work was to characterize the morphology of the siphunculi of the aphid Uroleucon ambrosiae (Thomas, 1878) (Hemiptera: Aphididae) by using scanning eletronic microscopy. The study was conducted in the laboratory of Nematology and Electron Microscopy, Plant Health Department, Universidade Estadual Paulista (UNESP), in the city of Jaboticabal, Brazil. The Uroleucon ambrosiae was collected in the field and, next, we prepared 5 samples from the aphids which were submitted to processes of preparation in order to be, afterwards, observed and photographed by Scanning Electronic Microscopy. Based on the studies, it was possible to observe that the siphunculi of U. ambrosiae presents tubular shape and rough appearance with an opening in the form of “U”. The morphological observations of this aphid’s siphunculi are a very important factor in the recognition of this species, helping in the differentiation of other existing aphids.